History of Introduction of Bivalent Human Papilloma Virus 16/18 Vaccine in Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Abstract not availableBangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 68-70